Mucosal and Systemic Immune Responses to Influenza H7N9 Antigen HA1–2 Co-Delivered Intranasally with Flagellin or Polyethyleneimine in Mice and Chickens - Song, Li; Xiong, Dan; Song, Hongqin; Wu, Lili; Zhang, Meihua; Kang, Xilong; Pan, Zhiming; Jiao, Xinan (Frontiers in Immunology, 2017)
Consecutive cases of human infection with H7N9 influenza viruses since 2013 in China have prompted efforts to develop an effective treatment. Subunit vaccines introduced by intranasal administration can block an infection at its primary site; flagellin (fliC) and polyethyleneimine (PEI) have been shown to be potent adjuvants. We previously generated the hemagglutinin (HA)1-2-fliC fusion protein consisting of the globular head domain (HA1-2; amino acids 62–284) of HA fused with Salmonella typhimurium fliC. In the present study, we investigated its effectiveness of both flagellin and PEI as mucosal adjuvants for the H7N9 influenza subunit vaccine. Mice immunized intranasally with HA1-2-fliC and HA1-2-PEI showed higher HA1-2-specific immunoglobulin (Ig)G and IgA titers in serum, nasal wash, and bronchial alveolar lavage fluid. Moreover, splenocyte activation and proliferation and the number of HA1-2-specific interferon (IFN)-γ- and interleukin (IL)-4-producing splenocytes were markedly increased in the fliC and PEI groups; in the latter, there were more cells secreting IL-4 than IFN-γ, suggesting that fliC induced T helper type (Th)1 and Th2 immune responses, and PEI induced Th2-biased responses, consistent with the serum antibody isotype pattern (IgG1/IgG2a ratio). Furthermore, virus challenge was performed in a chicken model. The results showed that chickens receiving fliC and PEI adjuvant vaccine exhibited robust immune responses leading to a significant reduction in viral loads of throat and cloaca compared to chickens receiving only HA1-2. These findings provide a basis for the development of H7N9 influenza HA1-2 mucosal subunit vaccines.